2010
DOI: 10.1042/bj20100330
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB mediates lipid-induced fetuin-A expression in hepatocytes that impairs adipocyte function effecting insulin resistance

Abstract: Fetuin-A, a hepatic secretory protein, has recently been implicated in insulin resistance and Type 2 diabetes. It is an endogenous inhibitor of insulin receptor tyrosine kinase. However, regulation of fetuin-A synthesis in relation to insulin resistance is unclear. In the present paper, we report that both non-esterified ('free') fatty acids and fetuin-A coexist at high levels in the serum of db/db mice, indicating an association between them. For an in-depth study, we incubated palmitate with HepG2 cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(139 citation statements)
references
References 35 publications
7
121
0
6
Order By: Relevance
“…In both genders, fetuin-A is positively correlated with IR (18). Therefore, fetuin-A may play an important role in the pathophysiology of T2DM (19). Our results are consistent with those described in previous studies (20,21).…”
Section: Discussionsupporting
confidence: 83%
“…In both genders, fetuin-A is positively correlated with IR (18). Therefore, fetuin-A may play an important role in the pathophysiology of T2DM (19). Our results are consistent with those described in previous studies (20,21).…”
Section: Discussionsupporting
confidence: 83%
“…Although it is unclear which factors regulate fetuin-A production, it was reported that free fat acids (FFAs) and hyperglycemia increase fetuin-A expression and induce insulin resistance (22). Ix et al (23) conducted a study to investigate the relationship between metabolic syndrome and fetuin-A on 711 patients with coronary artery disease having non-diabetic metabolic syndrome and found that the increase in fetuin-A level was associated to each component of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the induction of insulin resistance, fetuin-A promotes cytokine expression in human monocytes and reduces the expression of the atheroprotective adipokine-adiponectin in animals 8,9,46 . Moreover fetuin-A deteriorates free fatty acid uptake and storage in adipocytes 10 . A decrease in adiponectin levels that usually enhances oxidation of free fatty acids, observed in patients with coronary artery disease or with at high risk for CVD, may increase free fatty acid levels and lead to worsening atherosclerosis 12,24,28 .…”
Section: Fetuin-a As a Marker Of Cardiovascular Diseasementioning
confidence: 99%
“…It also accumulates in bones and teeth as a major fraction of noncollagenous bone proteins and regulates bone remodeling and calcium metabolism being an important inhibitor of calcium salt precipitation and calcification in vivo 2,7 . Fetuin-A has adipogenic properties, reduces expression of the atheroprotective adipokine-adiponectin and deteriorates free fatty acid uptake and storage in adipocytes 3,8,10 . Therefore fat accumulation in the liver may be associated with higher levels of fetuin-A (ref.…”
Section: Introductionmentioning
confidence: 99%